Attitude of University-level Students of the Faculty of Education Towards Sports and Physical Activity - Bohara, Kishore; Chiluwal, Shailandra; Thapa, Suresh Bahadur (Journal of Research in Education, 2025)
This paper tries to investigate the attitudes of university-level students enrolled in the Faculty of Education toward sports and physical activity. In a descriptive quantitative research design, participants’ attitudes were gauged through a structured Likert scale comprising 20 statements, both positive and negative, about sports and physical activity. The sample size consisted of 150 students and was divided equally between those enrolled in Health and Physical Education programs and those from other specializations. The results indicated a generally positive attitude towards sports and physical activities for both groups, though the overall mean scores for HPE students were higher compared to non-HPE students. The analysis of attitudes shows significant statistical differences; therefore, these favorable attitudes are made because of greater knowledge and involvement in sports and physical activities. Results emphasize the need for increasing physical activity within educational curricula, since it will increase the engagement of students and improve their lives. Recommendations for policy implementation to integrate sports and physical activities into educational programs are discussed to foster positive health behavior.